Prevalence and correlates of diabetes mellitus among homeless veterans nationally in the Veterans Health Administration. Issue 2 (2nd July 2016) - Iheanacho, Theddeus; Rosenheck, Robert
Abstract: Background : Homeless people are at high risk for many chronic medical conditions although their risk of diabetes has not been well studied. Current epidemiological studies of diabetes prevalence among homeless adults have been based mostly on self-report data not supported by clinical assessments. Objectives : To determine the prevalence and risk factors for diabetes mellitus (DM) among homeless veterans in the Veteran Health Administration (VHA). Methods : The sample included 3 464 364 veterans with documented body mass indexes (BMI), 137 720 (4%) of whom had been homeless. Logistic regression models were used to determine the odds of having DM among homeless veterans compared to non-homeless veterans. Bivariate and multi-variate analyses were then used to identify potential risk factors for DM among homeless veterans. Results : The prevalence of DM in homeless veterans was 19%. Homeless veterans with DM, compared to those without it were older, more likely to have a BMI > 40 and more likely to have DM-related co-morbidities. Conclusions : There is a high prevalence of DM among homeless veterans in the VHA compared to previous reports for homeless adults (8%). Tailored approaches to improve access to DM screening, prevention, and treatment could benefit homeless veterans.